KINERJA BALAI BESAR PENGAWAS OBAT DAN MAKANAN DALAM PENGAWASAN PEREDARAN KOSMETIK ILLEGAL DI PEKANBARU - Ambok Upek; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The problem regarding the Illegal Cosmetics Circulation in Pekanbaru is interesting to discuss because I have seen that from the past year many business actors have started to appear selling various kinds of cosmetic products that are traded in Pekanbaru, The purpose of this study was to determine how far the supervision carried out by the POM Center in supervising the distribution of cosmetics in Pekanbaru. This research uses descriptive qualitative research methods through data collection techniques by means of observation, interviews and documentation in the form of pictures or tables The results of this study are based on the theory of Agus Dwiyanto which includes Productivity, Service Quality, Responsibility and Accountability. The informants in this study were the Head of the Pekanbaru City Drug and Food Control Center, the staff of the Food and Drug Administration for Research, Cosmetics Business Actors. , Society, Performance Implementation Center for Drug and Food Control has not run optimally as I see there are still many illegal cosmetic products circulating in Pekanbaru, the supervision carried out by the POM Center has not been maximally yet also found obstacles in the implementation of the supervision of illegal cosmetic products namely limited budget, unequal human resources, competence and quality of employees who are not evenly distributed Keywords: Performance, Supervision, National Agency of Drug and Food Control